2007
DOI: 10.1105/tpc.106.044602
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of Gibberellins by Arabidopsis GAMT1 and GAMT2

Abstract: Arabidopsis thaliana GAMT1 and GAMT2 encode enzymes that catalyze formation of the methyl esters of gibberellins (GAs). Ectopic expression of GAMT1 or GAMT2 in Arabidopsis, tobacco (Nicotiana tabacum), and petunia (Petunia hybrida) resulted in plants with GA deficiency and typical GA deficiency phenotypes, such as dwarfism and reduced fertility. GAMT1 and GAMT2 are both expressed mainly in whole siliques (including seeds), with peak transcript levels from the middle until the end of silique development. Within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
206
2
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 236 publications
(217 citation statements)
references
References 51 publications
5
206
2
4
Order By: Relevance
“…Quantification of Endogenous ABA and GA Levels GA measurements were performed on a liquid chromatography-tandem mass spectrometry system consisting of a quadrupole/time-of-flight tandem mass spectrometer (Q-Tof Premier; Waters) and an Acquity Ultra Performance liquid chromatograph (Waters) equipped with a reversephase column (Acquity UPLC BEH-C18; Waters), as described previously (Varbanova et al, 2007). 2 H-labeled GAs (purchased from Lewis Mander, Australian National University) were used as internal standards.…”
Section: Germination Assaymentioning
confidence: 99%
“…Quantification of Endogenous ABA and GA Levels GA measurements were performed on a liquid chromatography-tandem mass spectrometry system consisting of a quadrupole/time-of-flight tandem mass spectrometer (Q-Tof Premier; Waters) and an Acquity Ultra Performance liquid chromatograph (Waters) equipped with a reversephase column (Acquity UPLC BEH-C18; Waters), as described previously (Varbanova et al, 2007). 2 H-labeled GAs (purchased from Lewis Mander, Australian National University) were used as internal standards.…”
Section: Germination Assaymentioning
confidence: 99%
“…However, it is not clear to what extent this is a general mechanism that occurs in other plant species. Secondly, methyl transferases specific for GAs have been described in Arabidopsis thaliana, where expression is mainly localized to developing seeds, and analysis of loss-offunction mutants suggests a role in GA inactivation in seed tissues (Varbanova et al, 2007), although accumulation of methylated GAs has not yet been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…SAMT and BAMT belong to a protein family called the SABATH [7]. In addition to SA and BA, other known carboxylic acid substrates of the SABATH family include jasmonic acid (JA) [34], indole-3-acetic acid [31,44e46], gibberellic acids [41], farnesoic acid [42], cinnamic acid and p-coumaric acid [16] and loganic acid [21]. Other members of the SABATH family are involved in caffeine biosynthesis by catalyzing nitrogen methylation [25].…”
Section: Introductionmentioning
confidence: 99%